2017
DOI: 10.1016/j.conbuildmat.2017.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of heating rate effect on spalling of high-performance concrete under high temperature conditions

Abstract: High-performance concrete (HPC) is vulnerable to spalling under high temperature conditions and it has been found that the heating rate can exert a tremendous effect on spalling of HPC. To prevent HPC from spalling, the heating rate effect should be understood.However, quantitative analyses are still lacking and the heating rate effect has not been well interpreted so far. In this paper, a numerical analysis of the heating rate effect on spalling of HPC is presented. Based on the experimental results reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Similar conclusions have been illustrated by other studies [3,9]. Further, a large number of researchers indicated that the heating temperature [3,9,10], heating rate [11] and cooling regimes [12,13] all have a significant influence on the microstructure and performance of concrete.…”
Section: Introductionsupporting
confidence: 85%
“…Similar conclusions have been illustrated by other studies [3,9]. Further, a large number of researchers indicated that the heating temperature [3,9,10], heating rate [11] and cooling regimes [12,13] all have a significant influence on the microstructure and performance of concrete.…”
Section: Introductionsupporting
confidence: 85%
“…As basalt fibre plays a dominant role at 300 ºC and 800 ºC, PP fibre governs the flexural strength at 600 ºC where the elastic strain energy reaches maximum value due to the vapour pressure [25]. This is due to the same behaviour of PP fibre under high temperature as explained in Section 3.1.…”
Section: Flexural Strengthmentioning
confidence: 66%
“…An electric muffle furnace was used to heat 20 saturated specimens of each mixture [ 36 ]. Heating–cooling cycles consisted of three phases: temperature rise at 5 °C/min [ 30 , 57 , 58 , 59 , 60 ], temperature dwell corresponding to two hours at 600 °C to achieve thermal steady-state [ 61 ] and slow cooling to room temperature at about 0.5 °C/min to avoid thermal shock ( Figure 2 ). Saturated specimens were used to minimize possible effects of the moisture content on the heat and mass transfer properties of concrete, especially in the initial state [ 33 ].…”
Section: Experimental Programmentioning
confidence: 99%